2007
DOI: 10.1007/s11845-007-0036-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between nutrient intake and cognitive performance in people at risk of dementia

Abstract: The findings of this work suggest that dietary cholesterol and sodium intake may be linked to cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Of note, this is the first study of its kind to attempt to answer this important research question. It is known that patients with dementia and AD have poor diets lacking in fruit and vegetables [47][48][49] and therefore we know that, on average, patients with AD consume less carotenoids than patients free of AD. Furthermore, it has been shown that high serum concentrations of L+Z are associated with a lower risk of AD mortality in adults [50] and that plasma antioxidants are depleted in mild cognitive impairment and in AD when compared to subjects with normal cognitive function [51].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this is the first study of its kind to attempt to answer this important research question. It is known that patients with dementia and AD have poor diets lacking in fruit and vegetables [47][48][49] and therefore we know that, on average, patients with AD consume less carotenoids than patients free of AD. Furthermore, it has been shown that high serum concentrations of L+Z are associated with a lower risk of AD mortality in adults [50] and that plasma antioxidants are depleted in mild cognitive impairment and in AD when compared to subjects with normal cognitive function [51].…”
Section: Discussionmentioning
confidence: 99%
“…A small observational study of 44 adults (mean age 57) found that participants with lower MMSE scores reported significantly higher salt intakes than those with higher scores. 18 By contrast, two prospective studies in older adults 19,20 reported no association between dietary salt intake (assessed via food frequency questionnaires) and cognitive decline measured by the MMSE (Nowak et al, 2018;1,194 adults, mean age 74±3; 6.9 year follow-up) 18 or on measures of mild cognitive impairment and pre-dementia in women with hypertension or on antihypertensive medication (Haring et al, 2016;6,426 women aged 65-79; median follow-up 9.1 years). 19 In the latter study, cognitive impairment was strongly associated with hypertension, suggesting that effects of salt on cognition might be mediated by changes to vascular function.…”
Section: Investigation Of the Relationship Between Dietary Salt And Cmentioning
confidence: 99%
“…24 Whereas most studies control for total energy intake in their analyses, 17,20,21 others have not measured or adjusted for this factor. 18,22 In addition, differences in total energy intake likely correspond to higher intakes of refined carbohydrates and saturated fats that are themselves associated with cognitive impairment. 25 Taken together, this highlights a need for research testing the effects of salt consumption under tightly controlled conditions.…”
Section: Investigation Of the Relationship Between Dietary Salt And Cmentioning
confidence: 99%
“…Goodwin and colleagues showed that older adults with lower protein intakes had a lower score on verbal memory tests and nonverbal abstract reasoning than elderly adults who were better nourished [21]. Conversely, in a small study in first-degree blood relatives of AD patients (n = 44) no difference in protein intake was found between individuals with normal and individuals with low MiniMental State Examination (MMSE) scores [18]. In another study, performed with noncognitively impaired elderly persons, no difference in protein intake was observed between adequate and nonadequate scores on the MMSE and Pfeiffer's Mental Status Questionnaire (PMSQ) [20].…”
Section: Evidence From Observational Studiesmentioning
confidence: 99%